Women as an Emerging Actor in Peace and Security: The Impact of UNSCR 1325 in Albania - Jusufi, Islam; Zenelaj Shehi, Reina; Vila Zeka, Jubjana (Journal of Regional Security, 2022)
Implementing the United Nations Security Council Resolution 1325 (UNSCR 1325) on Women, Peace, and Security in practice is emerging as a priority for Albanian security politics, in which the Government of Albania is endeavouring to act by increasing compliance with the norms promoted by the Resolution. This article reflects on the implementation of the UNSCR 1325 by focusing on the discourse on mainstreaming the women, peace and security norms in Albanian society. It finds that the UNSCR 1325 contributed to the increase of gender-related content in Albanian political, academic and civil society elite discourse, albeit selectively. Albanian political, academic and civil society actors appear to have been less responsive to the responsibilities of the UNSCR 1325, predictably due to the fact that Albania is not a conflict or post-conflict country, the status of which the Resolution primarily addresses. In conditions that Albania has been more responsive, the focus has been more on issues of gender equality in general rather than being guided by the specific norms of the UNSCR 1325.